Second symposium on footwear biomechanics (1995)
This document records the short abstracts and other information concerning the Second Symposium of the International Society of Biomechanics Working Group on Functional Footwear. The Symposium attracted more than 70 specialists in biomechanics from around the world to the Deutsche Sporthochschule in Cologne, Germany, at the end of June 1995. The primary function of the Working Group on Functional Footwear is to provide a forum within the ISB for those interested in footwear biomechanics. The Working Group currently comprises more than one hundred members from North America, Europe, Japan and Australasia. The Working Group aims to encourage research and promote discussion of biomechanical issues related to footwear, including sports shoes, clinical and prescription footwear and footwear designed for special purposes. This Symposium was the second in the group's brief history. The first was held in August of 1994, in conjunction with the Canadian Society of Biomechanics biennial meeting in Calgary. The main objective of these meetings is to promote the exchange of ideas and to provide opportunities for extended discussion. Building on the format of the Calgary Symposium, this meeting included a mixture of original papers, work in progress, invited presentations and an open forum. Two prizes were awarded at the end of the Symposium. A prize valued at US$ 1000 was presented by adidas AMERICA, Inc., and awarded in recognition of the original paper which, in the view of the adjudicators, made the most significant contribution to footwear biomechanics research. In addition, a "New Investigator's Award", valued at DM 1000 was presented by novel gmbh and awarded to the authors of the most significant contribution based on work conducted as part of a Masters or Doctorate degree. A volume of more extended (2 page) abstracts will be published later in 1995. Availability will be announced on the Working Group home page and on the Biomechanics List Server, biomch-L.